National and International Policies and Policy Instruments in the Development of Agroforestry in Chad - Foundjem-Tita, D.; Degrande, A.; Kamdem, C.B. (MDPI, 2021)
The potential of agroforestry to improve livelihoods and mitigate climate change and environmental degradation has been widely recognized, especially within the context of climate-smart agriculture. However, agroforestry opportunities have not been fully exploited because of several reasons, among which are adverse policies and legislations. However, many countries do not have a full understanding of how their policy and institutional environment may affect agroforestry development. We aim to fill this gap by looking at the particular case of Chad. The method used included examining data from: (i) literature reviews of important national and international polices, strategies, and legislation governing access to land and trees, among which are ‘La Loi 14’, Chad’s 2010 poverty reduction strategy paper, draft zero of the National Environmental Policy, (ii) interviews and focus group discussions with NGOs, government officials, and farmers, and (iii) surveys with 100 households. Results show that Chad has no specific agroforestry policy but opportunities for agroforestry can be found in some of the above-mentioned policy documents and government strategies. Most stakeholders interviewed had positive attitudes towards agroforestry, but uptake of the practice is handicapped by poor understanding of the forestry law by farmers and forestry officials. Gaps in existing laws give room for rent-seekers to collect individual (USD 272–909) and collective (USD 36–1818) access fees to trees on both forest and farmland. We propose that the government of Chad should unmask elements of agroforestry in existing policies and policy instruments to demonstrate its importance in responding to livelihood and environmental challenges in the country.